Transmission tower classification based on landslide risk map generated by Geographical Information System (GIS) at Cameron Highlands - Hazwani N.K.; Rohayu C.O.; Fathoni U.; Baharuddin I.N.Z.; Azwin Z.A. (Institute of Physics Publishing, 2023)
Transmission tower is usually locates at remote area which is covered by hilly topography. Landslide is mainly occurring at hilly area and causing failure to the tower structure. This phenomenon subsequently will affect the national electricity supply. A landslide risk hazard map is generated using Geographical Information System (GIS). Risk classification is introduced to initiate the monitoring process along Jor-Bintang transmission line, Cameron Highland, Pahang. The classification has been divided into three categories, which are low, medium and high. This method can be applied in slope monitoring activities since all towers have been classified based on their risk level. Therefore, maintenance schedule can be planned smoothly and efficiently. Published under licence by IOP Publishing Ltd.